Design of a Broadband Radome-Enclosed Dual-Polarization Antenna Array Covering Sub-6 GHz Band with Differential Feeding - Zhirong An; Mang He (International Journal of Antennas and Propagation)
A differentially fed dual-polarized antenna with low cross-polarization is proposed for sub-6 GHz applications. The main patch is fed through two pairs of symmetrical ports, and annular-ring slits are etched around the feedings. The broadband 180° phase shifter provides a stable differential feeding structure, and a 1 mm thick radome with a parasitic patch printed on its inner surface is utilized to expand the impedance bandwidth. The impedance bandwidth of the proposed antenna ranges from 3.3 to 6.0 GHz, covering the entire sub-6 GHz band. The 4-element antenna array features low profile, wide bandwidth, low cross-polarization level, and stable gain over the entire operating band. The prototype of the antenna array is fabricated and measured, and the design is well validated by experimental results.